Four Shades of Feedback: The Content of Feedback from Faculty Supervisor, Cooperating Teacher, Peers and Students in Practice Teaching and Its Effects on Self-Reflection and Self-Regulation - Takkaç Tulgar, Ayşegül (Alberta Journal of Educational Research, 2019)
This qualitative case study, grounded on self-reflection and self-regulation framework, investigated the content and scope of feedback provided by cooperating teachers, faculty supervisor, peers and students in the practicum school and the influence of feedback on preservice teachers’ self-reflection and regulation skills. The participants were 28 senior preservice teachers who attended Practice Teaching course. The data was collected through written feedback reports by the cooperating teacher, faculty supervisor, peers, and the students; it included reflection reports and the answers to open-ended questions by participants. The results of the content analysis revealed that the feedback by cooperating teacher, peers, and students centred on similar aspects. An evaluation of the performer’s behaviours, attitudes, and actions formed the what side, while the faculty supervisor provided feedback with more comprehensive content referring to the what, why and how aspects in the performance. The three types of feedback provided a chance for the participants to reflect-on-action, while the supervisor’s feedback indirectly promoted reflection-in-action. Key words: feedback; teaching practice; self-reflection; self-regulation Cette étude qualitative de cas, axée sur un cadre d’autoréflexion et d’autorégulation, se penche sur le contenu et la portée de la rétroaction fournie par des enseignants coopérants, des pairs, des élèves et un superviseur de la faculté à l’école de stages, d’une part, et de l’influence de cette rétroaction sur les capacités d’autoréflexion et d’autorégulation des stagiaires, d’autre part. Les participants regroupaient 28 stagiaires seniors inscrits au cours de pratique de l’enseignement. Les données ont été recueillies par la lecture de rapports écrits constituant la rétroaction par les enseignants coopérants, le superviseur de la faculté, les pairs et les élèves. Les données comprenaient également des rapports d’introspection et des réponses à des questions ouvertes par les participants. Les résultats de l’analyse de contenu révèlent que la rétroaction de la part des enseignants coopérants, des pairs et des élèves portait sur des aspects similaires. L’évaluation des comportements, attitudes et actions des stagiaires répondait à la question du quoi alors que la rétroaction de la part du superviseur de la faculté répondait de façon plus globale au quoi, qui et comment du rendement des stagiaires. Le premier type de rétroaction offrait aux stagiaires l’occasion de réfléchir sur leur sur leur pratique d’enseignement alors que celle du superviseur leur donnait indirectement la possibilité de réfléchir pendant qu’ils pratiquaient l’enseignement. Mots clés : rétroaction; pratique d’enseignement; autoréflexion; autorégulation